2014
DOI: 10.1111/exd.12548
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lecithin retinol acyltransferase increases all‐trans retinoic acid levels and restores retinoid sensitivity in malignant melanoma cells

Abstract: Retinoids such as all-trans retinoic acid (ATRA) influence cell growth, differentiation and apoptosis and may play decisive roles in tumor development and progression. An essential retinoid-metabolizing enzyme known as lecithin retinol acyltransferase (LRAT) is expressed in melanoma cells but not in melanocytes catalysing the esterification of all-trans retinol (ATRol). In this study, we show that a stable LRAT knockdown (KD) in the human melanoma cell line SkMel23 leads to significantly increased levels of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Information on every GO term is provided in Table S1. As shown in Figure S6, several melanoma progression-related pathways, including oxidative phosphorylation (28,29), retinol metabolism (30)(31)(32), and ribosome (33,34), were significantly upregulated in the highrisk group (padj < 0.05). Collectively, the results obtained using the IRGP signature provide evidence of the molecular mechanisms affected by CM and, thus, the predictive power of this signature for the prognosis of CM patients.…”
Section: Biological Function Analysis In the High-risk Group Stratifimentioning
confidence: 99%
“…Information on every GO term is provided in Table S1. As shown in Figure S6, several melanoma progression-related pathways, including oxidative phosphorylation (28,29), retinol metabolism (30)(31)(32), and ribosome (33,34), were significantly upregulated in the highrisk group (padj < 0.05). Collectively, the results obtained using the IRGP signature provide evidence of the molecular mechanisms affected by CM and, thus, the predictive power of this signature for the prognosis of CM patients.…”
Section: Biological Function Analysis In the High-risk Group Stratifimentioning
confidence: 99%
“…Therefore, the restoration of the osteogenic ability of BMP9 in OS cells may contribute to the treatment of OS. ATRA promotes terminal differentiation of immature cells, including various types of cancer cells (25)(26)(27)(28)(29)(30), and can promote osteogenic differentiation (29)(30)(31)(32)(33)48). Yang et al reported that ATRA could inhibit proliferation, induce apotosis and promote osteogenic differentiation in 143B cells, but the effect of apotosis induced by ATRA is not obvious.…”
Section: Discussionmentioning
confidence: 99%
“…The biological effects of ATRA are mediated by two families of nuclear receptors, retinoic acid receptor (RAR) and retinoid X receptor (RXR), which work as RAR/RXR heterodimers and bind to retinoic acid response elements in the promoter regions of retinoid-responsive genes (24). ATRA can induce differentiation in acute promyelocytic leukaemia (APL) and other tumour types, such as neuroblastoma, breast cancer and melanoma (25)(26)(27)(28). Additionally, ATRA can induce osteoblastic differentiation of osteosarcoma cells both in vivo and in vitro (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…Information of every GO term is shown in Table S1. As shown in Figure S4, multiple melanoma progression-related pathways, including oxidative phosphorylation [24,25], retinol metabolism [26][27][28], and ribosome [29,30], were signi cantly upregulated in the high risk group (padj < 0.05). Collectively, these results provided evidence of molecular mechanisms affected by the IRGP signature and, thus, predictive of the prognosis of CM patients.…”
Section: Biological Function Analysis In High Risk Group Divided By 2mentioning
confidence: 99%